2020
DOI: 10.15419/bmrat.v7i1.583
|View full text |Cite
|
Sign up to set email alerts
|

Memory-enhancing effects of goat milk in D-galactose-induced aging rat model

Abstract: Introduction: Aging is a physiological process accompanied by cognitive decline, particularly in memory deterioration. D-galactose is a reducing monosaccharide which, if systemically exposed, causes accelerated senescence in several organs and is widely being used as an ideal agent to induce brain aging in animal models. Goat milk is a food of high nutritional value which has been demonstrated to possess strong antioxidant and anti-inflammatory properties. However, thus far, little is known of its possible eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…A parametric test was used to analyze data with a normal distribution and equal variance. One-way analysis of variance (ANOVA) followed by Tukey's post hoc test was used for multiple pairwise comparisons 28 . All values were expressed as mean ± standard error of the mean (SEM).…”
Section: Discussionmentioning
confidence: 99%
“…A parametric test was used to analyze data with a normal distribution and equal variance. One-way analysis of variance (ANOVA) followed by Tukey's post hoc test was used for multiple pairwise comparisons 28 . All values were expressed as mean ± standard error of the mean (SEM).…”
Section: Discussionmentioning
confidence: 99%
“…Cells Proliferation: [72] In-Vitro assays demonstrated that goat milk can counteract the effects of EAEC on cell renewal and repair the intestinal cell barrier function as goat milk contains higher concentrations of lysozyme hence offers additional protection. Memory-enhancing effects: [73] It has been observed that addition goat milk in the diet enhances the both long and short term memory performances along with spatial memory performance. It also prevents memory decline in the D-galactose plus goat milk treated group as compared to the control group where only Dgalactose was administered.…”
Section: Vitaminsmentioning
confidence: 99%
“…There have been very few investigations on the effects of goat milk and its by-products on the brain. According to research, goat milk and its products can increase learning and memory performance as well as protect them from memory deterioration, implying that goat milk has the ability to regulate memory processes (Safdar et al, 2020). Sialic acid, which is found in goat milk and colostrum, is also thought to be an important biologic component that aids in cognitive development and immunity in newborns (Kumar et al, 2016).…”
Section: Brain Developmentmentioning
confidence: 99%